La psychanalyse et la société de normalisation : Lacan versus Foucault - Aurélie Pfauwadel (Astérion)
In the 1970s, Foucault tied his genealogy of the society of normalization to his multiple genealogies of psychoanalysis. What is often misconstrued, however, is that Lacan himself related the emergence of psychoanalysis to the growing extension of the society of normalization, as a reaction to it, shortly before the publication of The Will to Knowledge (1976). Lacan’s position proves to be diametrically opposed to Foucault’s in that he considers psychoanalysis as a practice that lies radically beyond norms, and not as an agent of normalization. The crucial question treated by this article is, on the one hand, that of the pertinence of Foucault’s genealogies, and, on the other, that of pitting against this a credible history of psychoanalysis that would account for its specificity and its power of subversion. The tools of a history of psychoanalysis, furnished by Lacan, are of interest to this topic in many respects. He develops this history from within the field of psychoanalysis and in conformity with psychoanalytic epistemology, and, contrary to Foucault, he strives to maintain the necessity of thinking of psychoanalysis as a specific field in relation to other fields of knowledge and practices.